2009
DOI: 10.1002/cm.20416
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarization of the plasma membrane potential provokes reorganization of the actin cytoskeleton and increases the stability of adherens junctions in bovine corneal endothelial cells in culture

Abstract: In previous works we showed that the depolarization of the plasma membrane potential (PMP) determines a reorganization of the cytoskeleton of diverse epithelia in culture, consisting mainly of a reallocation of peripheral actin toward the cell center, ultimately provoking intercellular disruption. In view of this evidence, we explored in this study the possible effects of membrane potential hyperpolarization on the cytoskeletal organization and adherens junction (AJ) morphology and the stability of confluent b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 63 publications
4
30
0
Order By: Relevance
“…45,94 The cytoskeleton has also been identified by microarray analysis as a possible mediator of the depolarization response. This is supported by previous work demonstrating that V mem depolarization and hyperpolarization affect actin and tubulin cytoskeleton organization [95][96][97] and that ion transport proteins and cytoskeletal proteins can interact directly to regulate each other's functions. 98-100 GSEA also implicated mRNA processing and protein degradation, both of which have been shown to be regulated by depolarization in neurons.…”
Section: Discussionsupporting
confidence: 75%
“…45,94 The cytoskeleton has also been identified by microarray analysis as a possible mediator of the depolarization response. This is supported by previous work demonstrating that V mem depolarization and hyperpolarization affect actin and tubulin cytoskeleton organization [95][96][97] and that ion transport proteins and cytoskeletal proteins can interact directly to regulate each other's functions. 98-100 GSEA also implicated mRNA processing and protein degradation, both of which have been shown to be regulated by depolarization in neurons.…”
Section: Discussionsupporting
confidence: 75%
“…In MDCK cells, Vaaraniemi et al [126] found that activation of protein kinase C determined PMP depolarization and reorganization of the spectrin-based and actin cytoskeletons. Consistently with these findings, we showed that the nonspecific modifications of the PMP (i.e., depolarization or hyperpolarization) promote changes in the organization of the actin and tubulin cytoskeletons in bovine corneal endothelial (BCE) cells in culture [127, 128]. In particular, the changes observed for the actin cytoskeleton consisted, for the PMP depolarization, in a gradual loss of the peripheral ring, an increase in F-actin throughout the cytoplasm, appearance of intercellular gaps and, for sufficiently prolonged treatments, eventual cell detachment [127].…”
Section: Modulation Of the Epithelial Actin Cytoskeleton By Modifisupporting
confidence: 54%
“…45,94 The cytoskeleton has also been identified by microarray analysis as a possible mediator of the depolarization response. This is supported by previous work demonstrating that V mem depolarization and hyperpolarization affect actin and tubulin cytoskeleton organization [95][96][97] and that ion transport proteins and cytoskeletal proteins can interact directly to regulate each other's functions.…”
Section: Discussionsupporting
confidence: 75%